Musculoskeletal Ultrasound - Beggs, Ian (Wolters Kluwer, 2013)
Want to increase your imaging capabilities exponentially? Look no further than Musculoskeletal Ultrasound, an expertly crafted guide to ultrasound and musculoskeletal diagnosis. In this comprehensive book, you'll learn everything you need to know about employing powerful imaging techniques to produce precise and consistent readings. With clearly segmented and organized text, each topic is enhanced and supported by illustrations, photographs, and imaging scans. Assisted by the author and his world-renowned contributors, you'll focus on different parts of the body, as chapter subjects range from the shoulder, to the elbow, to the hand and wrist, as well as the muscles, nerves, and more. Witness how radiology specialists and practitioners are increasing their knowledge and expertise of the anatomy, pathophysiology, clinical presentation, and techniques of this imaging tool. Under the guidance of Musculoskeletal Ultrasound, you can acquire the skills you need to offer insightful, effective imaging diagnosis and outstanding medical treatment.